Affective measures: self-measurement and gridding in female cancer patients' storytelling practices on Instagram. Issue 1 (2nd January 2019) - Stage, Carsten
ABSTRACT: This article explores the interplay between various forms of self-measurement and affective processes in three female cancer patients' storytelling on Instagram. It argues that self-measurement should be approached as an epistemic, relational, biopolitical and affective practice of valuation, which simultaneously produces knowledge about the self, enacts social and technological relations, reproduces bodily discourses and motivates affective modulation. In the three Instagram profiles studied, self-measurement appears to work according to two different logics: a logic of self-tracking that quantifies stages towards restitution and a logic of self-experimentation that 'visibilizes' bodily surface changes during illness. In terms of affect, self-tracking is primarily aimed at establishing a sense of hope – supported by encounters with followers and their displays of love and empathy – but it is also linked to frustration and fear when the goal of measurement is postponed or unreachable. Self-experimentation, on the other hand, takes part in processes that affectively relate to the aesthetically changing ill body – a mode of measurement that is less focused on temporal progression and more focused on exploring the vulnerable aliveness and changeability of the body during cancer by focusing on relations between present and past. Finally, the article discusses to what extent these two logics resonate with wider cultural and biopolitical transformations in which publicly visible and intensely circulated patient practices are increasingly those that are able to master and affectively 'grid' the destructiveness of illness while telling and sharing a story about it.